(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Indonesian Language Lessons are lessons that must be given in the world of education ranging from basic education to higher education. The problem that is currently emerging is that Indonesian language lessons are less attractive and less attractive to students in elementary schools. The purpose of this research is to develop an application of Indonesian language learning games for elementary school students with the Android Game-based prototyping method as a medium for learning Indonesian lessons in elementary schools to make it more interesting, and to help make it easier for students to understand Indonesian lessons well in the hope of making an educational atmosphere. interesting, fun, comfortable and can increase the value of students. The prototyping method is a software development method, in the form of a physical working model of the system and functions as an early version of the system. With this prototyping method, a system prototype will be produced as an intermediary for developers and users so that they can interact in the process of information system development activities. In order for the prototype making process to be successful, it is by defining the rules at an early stage, that is, the developer and the user must have an understanding that the prototype is built to define initial requirements. The prototype will be removed or added to its part so that it is in accordance with the planning and analysis carried out by the developer until the trial is carried out simultaneously along with the development process..